Peran Persepsi Dukungan Organisasi dan Kepuasan Kerja dalam Memprediksi Komitmen Organisasi Karyawan Generasi Y di PT. X - Ester Yuni; Hana Panggabean (Cakrawala Repositori IMWI, 2023)
The activity of working in a company exposes individuals to interactions between generations. Each generation has distinctive cultural characteristics of their group that provide a direction for thinking, feeling and behaving. Generation Y is currently the majority generation in the world of work who is known to find it difficult to survive in the workplace. This phenomenon is a strong indication of a low level of organizational commitment. The purpose of this study was to examine the role of perceived organizational support and job satisfaction in predicting organizational commitment of Generation Y employees at PT. X. This research uses quantitative methods with a correlational non-experimental research design. The research participants were taken using census sampling technique, totaling 149 people of generation Y. The research instruments were Allen & Meyer's Organizational Commitment Questionnaire (1991), Eisenberger's Perceived Organizational Support Questionnaire (2002), and Job Satisfaction Survey Spector (1997). The descriptive findings show that organizational commitment and perceived organizational support are at a high level while job satisfaction is at a moderate level. Perceived organizational support has a significant positive correlation with organizational commitment, while job satisfaction has no correlation with organizational commitment. The conclusion from this study is that perceived organizational support and job satisfaction significantly predict organizational commitment.